2012
DOI: 10.1155/2012/515962
|View full text |Cite
|
Sign up to set email alerts
|

HIV RNA Suppression and Immune Restoration: Can We Do Better?

Abstract: HAART has significantly changed the natural history of HIV infection: patients receiving antiretrovirals are usually able to control viremia, even though not all virological responders adequately recover their CD4+ count. The reasons for poor immune restoration are only partially known and they include genetic, demographic and immunologic factors. A crucial element affecting immune recovery is immune activation, related to residual viremia; indeed, a suboptimal virological control (i.e., low levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 148 publications
4
33
0
4
Order By: Relevance
“…Since the viral load is inversely correlated to the CD4 count, this could explain the association between a higher number of initial CD4 and suboptimal recovery at six months [1]. However, other authors reported the opposite, i.e.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since the viral load is inversely correlated to the CD4 count, this could explain the association between a higher number of initial CD4 and suboptimal recovery at six months [1]. However, other authors reported the opposite, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…The recovery of the CD4 count during this process occurs in three stages. In the first six months of treatment, a fast increase of 20 to 30 CD4 cells/mm 3 per month is observed [1,2]. Nevertheless, for some patients, the immune response during this phase is insufficient despite an undetectable viral load.…”
Section: Introductionmentioning
confidence: 99%
“…The greatest increases in CD4 count occur during the first year of ART initiation [4,5,8,9,10], especially in patients with low baseline CD4 count [11]. However patients with low CD4 count are more likely to take longer to return to normal CD4 count levels [5], and may remain at increased risk of opportunistic infection hence morbidity [12]. Two studies in resource-rich countries with a minimum follow-up time of 6 years have shown a significant increase in CD4 count among patients who initiated ART at lower CD4 count level compared to those who started ART at high CD4 count [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the slow immune reconstitution in SR patients was probably not due to lower baseline CD4 + T-cell counts as previously described in other studies (2,3) because the baseline CD4 + T-cell counts in NR and SR patients were not significantly different. Other factors such as a highly activated apoptotic T-cell compartments, residual viremia, and elevated levels of interleukin-7, a key cytokine necessary to regulate the proliferation and survival of circulating naä ƒve and memory T cells, likely influenced the lower CD4 + T-cell counts in SR patients after HAART, as proposed previously (4,(13)(14)(15).…”
Section: Discussionmentioning
confidence: 64%